Autoimmunity promotes chronic lymphocytic leukemia progression in an indolent disease model - Lisa Pfeuffer; Viola Siegert; Riccardo Trozzo; Katja Steiger; Roland Rad; Jürgen Ruland; Maike Buchner (Scientific Reports)
Abstract Chronic lymphocytic leukemia (CLL) is a heterogeneous B cell malignancy characterized by the accumulation of functionally incompetent B lymphocytes. Despite the availability of highly effective treatments, CLL remains incurable, and the factors contributing to disease progression are not fully understood. Autoimmune complications frequently arise in CLL patients and are associated with poor clinical prognosis. This study investigates the connection between plasma cell-mediated autoimmunity and CLL progression using a mouse model that expresses an active Receptor Activator of NF-κB (RANK) in B cells (RK mice), where autoimmune manifestations coexist with CLL. Transcriptional profiling of RANK-driven leukemic cells revealed a more indolent form of CLL compared to the classical TCL1 model. The discovery of near-identical CDR3 regions in both plasma and CLL cells of RK mice suggests a shared progenitor and antigen driving both conditions. Deletion of Blimp-1, which prevents plasma cell differentiation, initially enhanced B1/CLL formation in young mice but nearly halted CLL progression, highlighting the significant influence of autoimmune complications on disease outcomes. This research underscores the intertwined nature of autoimmunity and CLL, suggesting that targeting inflammatory pathways could offer therapeutic potential for managing both conditions.